Bingham Fluid Flow in the Entrance Region of a Pipe - Baioumy, Basma Mokhtar Hussein Mohamed (2019)
A Master of Science thesis in Chemical Engineering by Basma Mokhtar Hussein Mohamed Baioumy entitled, “Bingham Fluid Flow in the Entrance Region of a Pipe”, submitted in May 2019. Thesis advisor is Dr. Rachid Chebbi and thesis co-advisor is Dr. Nabil Abdel Jabbar. Soft and hard copy available.